2000
DOI: 10.1159/000046199
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in Chronic Hemodialysis Patients Receiving Intravenous Iron Dextran – A Comparison of Two Products

Abstract: Background: Parenteral iron therapy is required in a majority of chronic dialysis patients who are receiving recombinant human erythropoietin (r-HuEPO) in order to provide adequate iron for erythropoiesis. At this time, there are only two formulations of parenteral iron dextran available for clinical use in the USA. These two preparations of iron dextran have different physical and chemical characteristics that might affect the adverse events experienced by dialysis patients receiving iron dextran. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…One of the two patients with anaphylactoid reaction and the sole patient with anaphylaxis had shown sensitivity to imferon in the past, thereby suggesting a high cross-reactivity between dextran compounds of different molecular weight. Non-serious ADEs rates with ID were 15.92% per patient and 1.76% per exposure, which is similar to the studies of McCarthy et al [16] (12.2% per patient) and Barton [14] (13% per patient). We have included patients developing respiratory tract infection in view of the suspected toxic effects of parenteral iron on the host-defense mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…One of the two patients with anaphylactoid reaction and the sole patient with anaphylaxis had shown sensitivity to imferon in the past, thereby suggesting a high cross-reactivity between dextran compounds of different molecular weight. Non-serious ADEs rates with ID were 15.92% per patient and 1.76% per exposure, which is similar to the studies of McCarthy et al [16] (12.2% per patient) and Barton [14] (13% per patient). We have included patients developing respiratory tract infection in view of the suspected toxic effects of parenteral iron on the host-defense mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…In a review of suspected iron dextran AEs, Fletes et al 34 noted that AEs were 8.1 times more likely to occur with HMW ID, and concluded that serious AEs related to IV iron dextran were rare and appeared to depend on the specific formulation of IV iron dextran. Similar results were observed by McCarthy et al 35 in a study examining AEs in chronic hemodialysis patients receiving IV iron dextran. In the first study to demonstrate the benefit of IV iron in synergizing with ESAs in the management of chemotherapyinduced anemia, 81 of 157 patients received iron dextran either as a bolus or TDI.…”
Section: High Molecular Weight Iron Dextransupporting
confidence: 89%
“…HMW iron dextran has been linked to an increased risk of anaphylaxis and is no longer available. 65 An observational study of 189 women treated with LMW iron dextran in second and third trimester reported no severe adverse events and only 2% transient infusion reactions. 66 These results corroborated outcomes in other studies showing safety of LMW iron dextran, 67,68 which allows complete replacement of IV iron in a single infusion over 15 to 60 minutes.…”
Section: Hepcidinmentioning
confidence: 99%